Human work interaction design : work analysis and interaction design methods for pervasive and smart workplaces : 4th IFIP 13.6 Working Conference, HWID 2015, London, UK, June 25-26, 2015, Revised selected papers /: work analysis and interaction design methods for pervasive and smart workplaces : 4th IFIP 13.6 Working Conference, HWID 2015, London, UK, June 25-26, 2015, Revised selected papers. (2015) - Unknown
No abstract available